Analisis Faktor-faktor Determinasi Jasa Layanan Pembiayaan Syariah Pada LPDB - Amrizal, Amrizal; Siddiq, Abu Bakar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to analyze the factors determining services at Revolving Fund Management Institutions. The research uses secondary data in the form of time series data. The data analysis method used in this research is multiple linear regression analysis. This model is used to explain the relationship and influence of independent variables on the dependent variable using eviews 12. Multiple linear regression analysis in this research is used to determine the influence of Operational Cost Levels, People's Purchasing Power (Inflation), Principles of Justice and Properity (Business Sector), and Fair Competition (Tariffs for Similar Industry Services) on the determination of services at Revolving Fund Management Institutions for the 2020-2023 period. Based on the research results, it was found that only the business sector influences the determination of service rates for financing at Revolving Fund Management Institutions. Meanwhile, the variables Operational Costs, inflation and similar service rates do not have a significant influence in determining the service rates applied. This shows that Revolving Fund Management Institutions are more focused on providing services by paying attention to the business sector in determining service rates. The business sector consideration is a form of justice and propriety, where businesses run by the community vary according to business scale, turnover and income/profits.